SANTIAGO MUNEZ’S PERSISTENCE AND THE RISKS IN DANNY CANNON’S FILM, GOAL! THE DREAM BEGINS; 2005 - Priyoto Priyoto (STIBA IEC JAKARTA, 2019)
The objectives of this study are (1) to elaborate the factors that cause Hernan Munez’s family immigrate illegally from Mexico to United States of America, the internal and external factors that influenced them to move from their original country, Mexico to USA; (2) to analyze the reasons why Hernan Munez not want his son to be a soccer player. These factors include ones that are inherent in himself; and (3) to discuss the motivation of Santiago Munez to be a real professional football player. These ambitions that come from himself and from outside as well. This research uses qualitative method. It is to gain an understanding of the underlying reasons, opinions, and motivations. This movie tells how Hernan Munez Family commits illegal immigration from his original place, Mexico to new destination that is United State of America. Munez wants to prove to his father that he can get better life if he does it seriously. His character is a very tough lad. He likes to learn from the mistakes and give the best result for himself, his team mate, club, and especially his beloved family. His large passion and dedication make his dream comes true